Occasional Word Formation in the Expressiveness of a Text - Vasyl Hreshchuk (Vasyl Stefanyk Precarpathian National University, 2022)
The article analyzes the contribution of occasional word formation to the expressiveness of the text. Making the text more expressive by means of an occasional word-formation takes place when the process of text creation involves a coining of a new word which violates the norms of lexical derivation in its structural and semantic parameters. Due to its optional, new, non-normative, functional one-time nature, occasional derivatives (coinages) have become one of the major linguistic means of forming the connotative component of the semantics of the text or its segment. An occasionally derived word appears as a result of a combination of common word-forming components, characteristic for a particular linguistic system, i.e. a creative basis and a derivational formant, but their interaction in a particular derivative may result in the expansion of internal valence and pushes it beyond the language norm. The article focuses on a detailed description of the non-normative interaction of common creative bases and forms within the main parts of speech and word formation methods as well as their role in the expressiveness of the text. The article also describes less common ways of forming the linguistic expression of the text by means of occasional coinages. The latter methods include the use of word-forming formats stylized according to the derivational means of another language present in the text, permutation of formative bases which are the components of a word-forming structure, the amalgamation of several prefixes, which either strengthen the meaning of the first one or neutralize the value of the following prefix. Emotionally colored occasional derivatives (coinages) constitute an important component of text creation as they are responsible for the pragmatic sphere of the text which is connected with the subjective modality of the text and its realization.